2012
DOI: 10.1038/pr.2012.117
|View full text |Cite
|
Sign up to set email alerts
|

Childhood IQ, hearing loss, and maternal thyroid autoimmunity in the Baltimore Collaborative Perinatal Project

Abstract: Background: Maternal thyroid autoantibodies during pregnancy have been implicated in neurodevelopmental delays, including early childhood cognitive deficits. We evaluated whether maternal autoantibodies to thyroid peroxidase (TPOaabs) during late pregnancy were associated with childhood intelligence quotient (IQ) scores in their offspring and how the children's TPOaab-associated sensorineural hearing loss (hL) might affect the result. Methods: We evaluated banked third-trimester sera corresponding to 1,733 chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…28 It is not clear why an elevation in thyroid autoantibodies in women who are euthyroid is associated with changes in neurodevelopment. 40 Although age did not differ significantly between negative and positive maternal TPO antibody status in some of these studies, 37,39 and in other studies, they corrected for maternal age, 38 it is important to note that many women with thyroid antibodies also have increased maternal age which itself is a risk factor for adverse outcomes and may confound the findings. 41 In summary, maternal thyroid dysfunction has been shown to be…”
Section: Associations Of Hypothyroidism With Brain Structure and Nementioning
confidence: 73%
See 2 more Smart Citations
“…28 It is not clear why an elevation in thyroid autoantibodies in women who are euthyroid is associated with changes in neurodevelopment. 40 Although age did not differ significantly between negative and positive maternal TPO antibody status in some of these studies, 37,39 and in other studies, they corrected for maternal age, 38 it is important to note that many women with thyroid antibodies also have increased maternal age which itself is a risk factor for adverse outcomes and may confound the findings. 41 In summary, maternal thyroid dysfunction has been shown to be…”
Section: Associations Of Hypothyroidism With Brain Structure and Nementioning
confidence: 73%
“…There are some data that thyroid autoantibodies may affect neurodevelopmental outcomes, separate from premature delivery effects. 28,[37][38][39][40] Cohort studies have shown increased sensorineural hearing loss and higher risk of ADHD even after correcting for TSH. 37,38 Studies have also shown an increased odds of ASD with positive thyroid autoantibodies with no difference between hypothyroid and euthyroid participants.…”
Section: Associations Of Hypothyroidism With Brain Structure and Nementioning
confidence: 99%
See 1 more Smart Citation
“…After screening the titles and abstracts, 22 studies were further assessed for eligibility by reading full-text [12][13][14][15][16][17][18][19]. After reviewing full-text, 15 articles were excluded because of not relevant design or lack of usable data [12,[23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Thus, seven prospective cohort studies were finally included into the metaanalysis [13][14][15][16][17][18][19].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…What causes learning disabilities?. According to researches there are various factors that cause difficulties in learning including imperfect formation of ears and hearing senses that affect early learning as early as in the womb (Wasserman et al, 2012), imbalance brain chemical caused by the imperfection of neurotransmitter function (Healy, 2004), birth trauma and emotional trauma during developmental process which causes disability learning failure associated with sensory integration and executive functions of the brain (May-Benson et al, 2009), allergies and nutritional aspects that influence the performance of children at school (Phyllis, 2013).…”
Section: Introductionmentioning
confidence: 99%